STUDI PREFERENSI PENGELOLAAN PERPARKIRAN BERDASARKAN PELAYANAN, KETERSEDIAAN PRASARANA DAN RETRIBUSI DALAM MENUNJANG PAD KOTA MAKASSAR - Nur Khaerat Nur (Journal Techno Entrepreneur Acta, 2016)
In the management of parking during this run visible indicators that can be used as a benchmark as the low contribution of parking service on revenue of Makassar and still less professional and optimal management of parking. This study aims to determine the level of optimization of the application of the parking management system by operators of parking based on public perception and analyze the level of service and high availability of parking facilities in the city of Makassar. This research was conducted by direct interview to the community and the spread of random questionnaires to determine public perceptions of parking management that are run during this and subsequent analysis of the level of service and availability of parking infrastructure by taking samples of the two locations in the city of Makassar. From the results of research in getting that parking geometric arrangement resulted in the design markings on the road Bougainville Makassar park consists of 26 markers and 20 markers of motor cars, while road markings Pengayoman consists of 146 cars and 54 motorcycles markers. Overall capacity of the car park on the street Bougainville 104 vehicles/h, the capacity of the car park on the street Pengayoman the west as much as 584 vehicles/hour. Capacity motorcycle parking on the street Bougainville as many as 80 vehicles/hour, capacity bike parking on the street Pengayoman the west as much as 216 vehicles / hour. For availability of parking facilities in addition to marking problems of parking, availability of infrastructure such as parking signs, SRP and parking attendants in Bougainville and western aegis not ideal should be added and equipped. Potential revenue (PAD), which can be generated at the study site from the calculation of the accumulation of cars and motorcycles parked vehicles every 15 minutes in the span of 13 hours every day for a week total daily average of Rp. 1,657,346. The respondent's perception of the overall entry in the medium category. For the highest score obtained at a frequency of parking of vehicles in the parking lot was not authorized by a score of 1054. While the lowest score in the delivery of tickets, with a score of 716. Overall it can be concluded that the availability of parking infrastructures is lacking and parking management systems are still considered less than optimal.